An efficient chemoenzymatic cascade strategy for transforming biomass into furfurylamine with lobster shell-based chemocatalyst and mutated ω-transaminase biocatalyst in methyl isobutyl ketone-water. (February 2023) - Tang, Zhengyu; Li, Qing; Di, Junhua; Ma, Cuiluan; He, Yu-Cai
Highlights: Lobster shell as carrier was used to prepare solid acid for furfural production. Corncob was catalyzed to furfural (122.2 mM) at 170 °C for 30 min in MIBK-H2 O. Recombinant E. coli TFTS harboring robust mutant ω-transaminase was constructed. TFTS cell efficiently transformed furfural (300 mM) into furfurylamine (93.6 % yield). Corncob was chemoenzymatically converted to furfurylamine (0.46 g/g xylan). Abstract: To date, an efficient process for manufacturing valuable furan compounds from available renewable resources has gained great attention via a chemoenzymatic route. In this study, a sulfonated tin-loaded heterogeneous catalyst CLUST-Sn-LS using lobster shell as biobased carrier was prepared to convert corncob (75.0 g/L) into furfural (122.5 mM) at 170 °C for 30 min in methyl isobutyl ketone (MIBK)–H2 O biphasic system (2:1, v/v). To improve furfurylamine yield, a novel recombinant E. coli TFTS harboring robust mutant Aspergillus terreus ω-transaminase [hydrophilic threonine (T) at position 130 was site-directed mutated to hydrophobic phenylalanine (F)] was constructed to transform 300–500 mM furfural into furfurylamine (90.1–93.6 % yield) at 30 °C and pH 7.5 in MIBK-H2 O. Corncob was converted to furfurylamine in MIBK-H2 O with a high productivity of 0.461 g furfurylamine/(g xylan). This constructed chemoenzymatic method coupling bio-based chemocatalyst CLUST-Sn-LS and mutant ω-transaminase biocatalyst in a biphasic system could efficiently convert lignocellulose into furfurylamine.